PERANCANGAN DESIGN PROTOTYPE UI/UX APLIKASI RESERVASI RESTORAN DENGAN MENGGUNAKAN METODE DESIGN THINKING - Ratna Nur Fadilah; Dhian Sweetania (Asosiasi Dosen Muda Indonesia, 2023)
Many people use restaurants as a choice of place to hold events such as family meals, social gathering, birthdays, etc. Because there are many restaurants in several cities, if you want to hold an event, you must reserve a place in advance. Therefore an application is needed to reserve a restaurant. The design process uses the Design Thinking method which is carried out in 5 stages, namely empathize, define, ideate, prototype, and testing. This Design Thinking method starts from problem analysis and problem solving to testing using the usability testing method to evaluate the UX (User Experience) of the design. Current technological developments make all things not escape from technology. Reserving a restaurant can be made easier by an application. That way, to help understand the use of a restaurant reservation application, it is necessary to design a UI/UX prototype design for a restaurant reservation application. UI/UX design for restaurant reservation applications requires an attractive and interactive design.